PENGEMBANGAN PELABUHAN CRUISE TANAH AMPO SEBAGAI GERBANG PARIWISATA KABUPATEN KARANGASEM - Suteja, I Wayan; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 2 No 2 (2014): VOL 2, NO 2 (2014): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2014.v02.i02.p05)
ABSTRACT Karangasem is one of regency in Bali have much of tourism potential and tourism resources, so Karangasem developed Tanah Ampo Cruise Port  to optimalize the tourists visiting, because cruise tourism is one of type of tourism trend in the word.  Every tourism port in every country have quality facilities and and very support by tourism potential. Thus, in this study aims to determine the potential of the area as the location of Tanah Ampo cruise port development and to discusses  Tanah Ampo Cruise Port development as a tourism entrance in Karangasem. This study discusses the development of Tanah Ampo Cruise Port as the gateway of tourism at  Karangasem Regency. To discuss this study used a descriptive qualitative  method. The   types of data consist of qualitative and quantitative data  as well as primary and secondary data  sources. Data collected by  in-depth interviews, observation , documentation studies and literature studies. Tanah Ampo cruise port located in Banjar Dinas Tanah Ampo, Ulakan Village, Manggis District, Karangasem Regency, Bali Province . This location is very strategic and has tourism potential wich consists of the physical and  nonphisical potential. T anah Ampo Cruise Port development project is implemented in accordance with the applicable regulations of port development in Indonesia and in accordance with the regulations of Bali Provincial and Karangasem Regency. Tanah Ampo Cruise Port development became a transit point as well as a destination for tourists who travel by  cruise shi p . The development also aims to increase the tourist visits to Karangasem and the all of tousrist attraction in Bali. But i n the operational phase of the  Tanah Ampo Port has not reached target operated due to several constraints related to port facilities,  thus requiring evaluation  and repairing the fasilities to able to meet market demands .
Keywords: Potential, cruise tourism, tourism port development.